استخدام تقنيات الذكاء الاصطناعي في عملية المراجعة في ليبيا من وجهة نظر المراجعين الخارجيين (Comprehensive Journal of Science, 2025)
"This study aimed to identify the challenges and difficulties that external audit firms in Libya may face when implementing artificial intelligence (AI) techniques during the auditing process. Furthermore, it explored the potential contribution of AI in developing and enhancing the auditing process within these firms, from the perspective of external auditors working in Libyan audit offices. To achieve its objectives, the study adopted a descriptive-analytical approach, utilizing a questionnaire as the primary research instrument. The study reached several key findings, most notably that the use of AI applications in external audit firms in Libya faces significant challenges, including a lack of technological and linguistic qualifications among auditors, limited specialized training, high implementation costs, and the absence of regulatory legislation. Conversely, the results demonstrated that the use of AI techniques significantly contributes to developing and improving the quality of the external audit process by enhancing efficiency and accuracy, analyzing big data, detecting fraud, and improving supervisory procedures. Moreover, it supports compliance with international standards, which positively reflects on the reliability of financial statements and report quality, strengthens the governance role of auditing, and assists in making more rational professional decisions.